Workplace spirituality in law enforcement: a content analysis of the literature - Moran, Ramon (Journal of management, spirituality & religion, 2017)
Community protests alleging police officers excessive use of force in places like Ferguson, Missouri, the place of Michael Brown's controversial death from a policeman's bullet, has raised public awareness of the need to reform law enforcement culture. Identifiable challenges to policing include burnout, higher rates of depression and anxiety, a militaristic sub-culture, and the need for community policing. Workplace spirituality's holistic model in the context of law enforcement may contribute to police officer wellness and safety, but law enforcement lacks consensus on the definition, conceptualization, and operationalization of spirituality in its workplace. A content analysis of law enforcement literature was conducted to (1) explore and distil how workplace spirituality is viewed in law enforcement and training and (2) to propose new directions in the integration of workplace spirituality in policing. Workplace spirituality was associated with meaning making, policing values and ethics, spirituality, one's religious beliefs, and the construct of self-transcendence. Implications of the findings suggest workplace spirituality is operational as a process of coping with stressors aiming at police officer wellness, and/or as virtuous leadership for community policing. A paradigmatic model for police training was inferred from the convergence of stress management, leadership, community policing, police wellness and safety, policing effectiveness, and policing culture with workplace spirituality.